-6a+24=

Simple and best practice solution for -6a+24= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6a+24= equation:


Simplifying
-6a + 24 = 0

Reorder the terms:
24 + -6a = 0

Solving
24 + -6a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -6a = 0 + -24

Combine like terms: 24 + -24 = 0
0 + -6a = 0 + -24
-6a = 0 + -24

Combine like terms: 0 + -24 = -24
-6a = -24

Divide each side by '-6'.
a = 4

Simplifying
a = 4

See similar equations:

| 5+3=-4x+47 | | 6=6/10 | | 7y+12=3y-4 | | -4/3u-6=7/3u+8 | | -(4x-4)-(3x-5)+4=-9(x-1)-(2x+7)+3 | | -x-18= | | x+5-11=-3 | | (2v+9)(8-v)=0 | | 4x^3y+12x^2y-8xy= | | -(4x-4)-(3x-5)+5=-9(x-1)-(2x+7)+3 | | 6v+10=9v+9 | | 1+2x-x^2=0 | | 0.1(3.2+2x)+1/2(3-x/5)=0 | | 8x^3+18x^2-10x= | | X/31=17 | | -1.5-6x=26.7 | | 9/6=11/8 | | 3x+12-4= | | -1/3x=-5/6 | | 3(5x-2)=19 | | M-4-3m=-2m-3-1 | | (13x-6)-6(2x+2)=-6 | | 400+300/20 | | 0.5x+6=x+5/3 | | 2/x-2=-4/x+4+18/(x-2)(x+4) | | 2u-54=-u+21 | | 8a=65-100n | | 400+(15x200)/200 | | (6h-7)/h | | (-7/12)-(-3/8)=0 | | 4x+32=4x+26 | | (17x-9)-8(2x+4)=-5 |

Equations solver categories